Vessels Sing Their ARIAs: The Role of Vascular Amyloid in the Age of Aducanumab - Lukas Sveikata; Andreas Charidimou; Anand Viswanathan (2021)
We review the implications of the recently approved aducanumab amyloid-β immunotherapy for treating Alzheimer disease with comorbid cerebral amyloid angiopathy. In clinical trials, amyloid-β immunotherapy has been associated with a high rate of amyloid-related imaging abnormalities, potentially driven by coexisting cerebral amyloid angiopathy. Therefore, immunotherapy's efficacy in patients may be modified by coexisting cerebrovascular pathology. We discuss the contributions of cerebral amyloid angiopathy on the development of amyloid-related imaging abnormalities and propose strategies to identify cerebral amyloid angiopathy in patients considered for immunotherapy.